A unified approach to periodic solutions for a class of non-autonomous second order Hamiltonian systems. (April 2021) - Wang, Zhiyong; Zhang, Jihui; Chen, Mengxi
Abstract: This paper is dedicated to studying the periodic solutions of non-autonomous second order Hamiltonian systems. By virtue of control functions and the minimax methods in critical point theory, we propose a unified approach when the nonlinearity is unbounded while grows no more than | x | at infinity. We establish some new existence theorems on periodic solutions, which unify and generalize many previously known results in the literature.